Physical therapy in burn wound healing: Development of clinical prediction rules to identify the efficacy of pulsed electromagnetic therapy - Ahmed Mohamed Nagy; Shaimaa Mohamed Ahmed Elsayeh; Mohamed Bayoumi Ibrahim Bayoumi; Shimaa Mohamed Metawee; Omnia Saeed Mahmoud Ahmed; Karim Ibrahim Saafan (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.